Pengaruh Adversity Quotient Terhadap Pencapaian Akademik Pada Mata Pelajaran IPS - Ika Tija Yanti; Nikmah Nikmah; Lailatul Sakdiah (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2026)
This study aims to examine the effect of Adversity Quotient (AQ) on students’ academic achievement in Social Studies. AQ refers to an individual’s ability to face, manage, and overcome difficulties encountered during the learning process. Low academic achievement is often influenced by students’ limited ability to cope with learning challenges; therefore, it is necessary to identify internal factors that contribute to this condition. Accordingly, AQ is considered an important factor that needs to be addressed in improving the quality of learning. This study employed a quantitative approach involving 30 students from grades VII and VIII at SMPIT At-Thoyyibah, Ketangga Village, during the second semester of the 2024–2025 academic year. Data were collected through an AQ questionnaire and students’ Social Studies report scores. A simple linear regression analysis was used to test the research hypothesis. The results revealed a significant positive relationship between AQ and students’ academic achievement in Social Studies (r = 0.62, p < 0.01). Students with higher AQ tended to achieve better academic performance. These findings emphasize the importance of developing AQ to improve students’ learning outcomes.